Effects of sleeve gastrectomy and Roux-en-Y gastric bypass on the pharmacokinetics of gabapentin and pregabalin: A cohort study - Georgios Schoretsanitis; Hege-Merete Krabseth; Magnus Strømmen; Arne Helland; Olav Spigset (PLoS ONE, 2025)
Background Bariatric surgery may affect the pharmacokinetics of medications by altering the gastrointestinal physiology. Pharmacokinetic changes of first-line neuropathic pain medications such as gabapentin and pregabalin following bariatric treatment have barely been investigated. Methods In our prospective five-case study we included gabapentin- or pregabalin-treated patients undergoing bariatric surgery at hospitals in Central Norway. Concentrations of gabapentin and pregabalin were assessed using serial blood samples over a dose interval, preoperatively and one, six and twelve months postoperatively. The primary outcomes of the study included changes in area under the time-concentration curve (AUC) with secondary outcomes comprising full pharmacokinetic profiling. Formal statistical testing was not performed due to few cases. Results Three pregabalin-treated obese patients undergoing Roux-en-Y gastric bypass (RYGB) and two gabapentin-treated patients undergoing RYGB (n = 1) and sleeve gastrectomy (SG) (n = 1) were included. Largest changes for dose-adjusted AUC values after surgery were seen in pregabalin-treated patients at one and six months (average increases of 53% one month and 28% 6 months postoperatively). In the patients on gabapentin, mean AUC changes were less than 10% from baseline throughout the study period. The inter-individual variation was high. Conclusion Postoperative pharmacokinetic changes for gabapentin were minimal, but for pregabalin we observed more pronounced changes, particularly in one patient. Due to few cases, the results should be interpreted with caution. Given the large inter-individual variation, therapeutic drug monitoring could be considered to capture pharmacokinetic changes and guide dose adjustments postoperatively.